The Effectiveness of Using Baamboozle Learning Media in Increasing Learning Motivation of Fourth Grade Elementary School Students - Sri Mita Yeni Girsang; Emelda Thesalonika; Muktar Panjaitan (EDUPEDIA Publisher, 2026)
Purpose – This study aims to address the low learning motivation of fourth-grade students in Science and Social Studies (IPAS), which stems from teaching methods dominated by lectures and a lack of interactive technological media. Methodology – The research method employed is a quantitative approach with a One-Group Pretest-Posttest experimental design. The subjects of this study were fourth-grade students at SD Negeri 091608 Sinaksak. Data collection techniques included validated learning motivation questionnaires and documentation. Findings – Data analysis was performed using normality tests, Paired Sample T-Tests, and effectiveness tests using the N-Gain Score, facilitated by SPSS 26 and Microsoft Excel. The results indicate a significant increase in learning motivation following the implementation of Baamboozle. Novelty – The average student scores improved from the pretest range of 53–78 to a posttest range of 86–99, with an average increase of 29.16 points. Hypothesis testing yielded a Sig. (2-tailed) value of 0.000 < 0.05 and a t-value of 18.723, which is greater than the t-table of 2.064, meaning that Ha is accepted. Significance – Based on the effectiveness test, the average N-Gain Score obtained was 0.77, categorized as High and Effective (77%). In conclusion, the use of Baamboozle as a learning medium is effective in increasing the learning motivation of fourth-grade students at SD Negeri 091608 Sinaksak.